2019
DOI: 10.1111/pbi.13143
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of a floral mutant reveals the mechanism of hooked petal morphogenesis in Chrysanthemum morifolium

Abstract: Summary The diversity of form of the chrysanthemum flower makes this species an ideal model for studying petal morphogenesis, but as yet, the molecular mechanisms underlying petal shape development remain largely unexplored. Here, a floral mutant, which arose as a bud sport in a plant of the variety ‘Anastasia Dark Green’, and formed straight, rather than hooked petals, was subjected to both comparative morphological analysis and transcriptome profiling. The hooked petals only became discernible during a late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…By WGCNA and KEGG pathway enrichment analyses, we determined that the green color of chrysanthemum ray florets is influenced by both chlorophyll metabolism and photosynthesis, as indicated by the enrichment of the “Photosynthesis”, “Carbon fixation in photosynthetic organisms”, “Photosynthesis-antenna proteins”, “Carbon metabolism”, and “Glyoxylate and dicarboxylate metabolism” KEGG pathways. Similar results were reported for the chrysanthemum variety “Anastasia Dark Green” and its white-flowered bud sport, in which genes related to the photosystem, thylakoid, plastid, and chloroplast were differentially expressed between samples with green and white ray florets [ 42 ].…”
Section: Discussionsupporting
confidence: 82%
“…By WGCNA and KEGG pathway enrichment analyses, we determined that the green color of chrysanthemum ray florets is influenced by both chlorophyll metabolism and photosynthesis, as indicated by the enrichment of the “Photosynthesis”, “Carbon fixation in photosynthetic organisms”, “Photosynthesis-antenna proteins”, “Carbon metabolism”, and “Glyoxylate and dicarboxylate metabolism” KEGG pathways. Similar results were reported for the chrysanthemum variety “Anastasia Dark Green” and its white-flowered bud sport, in which genes related to the photosystem, thylakoid, plastid, and chloroplast were differentially expressed between samples with green and white ray florets [ 42 ].…”
Section: Discussionsupporting
confidence: 82%
“…CmCYC2 controls ray floret identity in chrysanthemum 20 , and we found the CmCYC4 homolog (CL4616.Contig3_All) also had relatively low expression, suggesting that it also plays a role in regulating the degree of chrysanthemum ray floret fusion. The MADS-box transcription factor plays an important role in flower development because it regulates the characteristics of floral organs and influences their subsequent development 26 . Homologs of the Agamous-like MADS-box protein and MADS-box transcription factor were differentially expressed, with CmBES1 being overexpressed.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a previous report [ 45 ], we selected four stages of underground flower development in E. japonicum , and samples from each stage were subjected to transcriptomic profiling. A similar approach for exploring transcriptomic profile for floral differentiation has been adopted in different species such as Ranunculus glacialis [ 60 ], Chrysanthemum morifolium [ 61 ], Chrysanthemum lavandulifolium [ 62 ], Staphisagria Ranunculaceae [ 63 ], rice [ 64 ], and Delphinieae [ 63 ]. The obtained results in this study suggested significant variation in the expression profiles at the different stages.…”
Section: Discussionmentioning
confidence: 99%